Pengembangan Prototype Sistem Informasi Akademik Menggunakan Model Logical Record Structure (LRS) - Azhar Andika Putra; Rudiansyah; Sutra Romadon; Lemi Iryani (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
Traditional methods of recording data are often prone to errors that impact the inefficiency of the reporting process. Therefore, a system is needed to simplify data handling, minimize errors, and increase efficiency. The utilization of information technology has not been maximized, so they still use manual systems in various activities, such as administration, attendance, evaluation, and data collection. This causes several problems, including inaccurate data, repetition of data, and errors in calculations. The paper-based system also makes it difficult to manage data in the long term. This research aims to build a prototype academic information system at SMK YP Gadjah Mada Palembang using the logical record structure (LRS) model. This system is expected to increase efficiency and effectiveness in academic data management. Based on calculations using the system usability scale (SUS), the overall score is 632. The total amount after multiplying by 2.5 is 1577.5. The SUS value obtained is 105.1, indicating a high level of ease of use of the system.